Study of over-examination on tire induced by pressure correction process in flywheel tests. (July 2023) - Wang, Congwen; Xiao, Chi; Feng, Yihui; Dai, Yujing; Wang, Jun; Huan, Yan; Huan, Yong
In this paper, the strain energy density (SED) is used to study the over-examination to tire in flywheel test induced by pressure correction process. Flywheel test is the main method for evaluating tire durability, which cannot be measured on flat ground due to the variable road conditions. "Pressure Correction" is a necessary step in flywheel tests, but this process can lead to an over-examination of tire durability, which means the tire durability will be underestimated. However, it is impossible to obtain the tire durability from ideal flat ground test, so this paper utilizes the finite element method (FEM) to simulate the tire rolling condition on flat ground and differently sized flywheels, and the SED is used to evaluate the over-examination of tire durability in flywheel test. According to the results, a flywheel with too small diameter has a large amount of over-examination, and the amount caused by a large flywheel is acceptable. This methodology can be a guideline to assess the over-examination on different sized flywheel tests relative to the flat ground, and for the certain tire in this study, flywheels with 3–5 times the tire diameter appear to have an acceptable over-examination.